Self-healing, stretchable and robust interpenetrating network hydrogels. (21st September 2018) - Macdougall, Laura J.; Pérez-Madrigal, Maria M.; Shaw, Joshua E.; Inam, Maria; Hoyland, Judith A.; O'Reilly, Rachel; Richardson, Stephen M.; Dove, Andrew P.
Abstract : A self-healable, mechanically strong and stretchable hydrogel network that supports cell encapsulation is reported to be achieved by creation of an interpenetrating network approach between PEG and natural polymers. Abstract : A self-healable stretchable hydrogel system that can be readily synthesized while also possessing robust compressive strength has immense potential for regenerative medicine. Herein, we have explored the addition of commercially available unfunctionalized polysaccharides as a route to synthesize self-healing, stretchable poly(ethylene glycol) (PEG) interpenetrating networks (IPNs) as extracellular matrix (ECM) mimics. The introduction of self-healing and stretchable properties has been achieved while maintaining the robust mechanical strength of the orginal, single network PEG-only hydrogels (ultimate compressive stress up to 2.4 MPa). This has been accomplished without the need for complicated and expensive functionalization of the natural polymers, enhancing the translational applicability of these new biomaterials.